Systematic review and meta-analysis of Veress needle entry versus direct trocar entry in gynecologic surgery. Issue 1 (28th June 2022) - Marchand, Greg J; Masoud, Ahmed; King, Alexa; Brazil, Giovanna; Ulibarri, Hollie; Parise, Julia; Arroyo, Amanda; Coriell, Catherine; Goetz, Sydnee; Moir, Carmen; Christensen, Ashley; Alexander, Tia; et al.
Abstract : Objective: Although many studies have been performed, no consensus exists as to the ideal entry for laparoscopic gynecologic surgery. We sought out to compare the safety of direct trocar insertion with that of the Veress needle entry technique in gynecologic laparoscopic surgery. Design: Systematic review with meta-analysis. Setting: We searched Medline, ClinicalTrials.Gov, PubMed, Cochrane CENTRAL, SCOPUS, and Web of Science from their inception through 31 July 2021 for relevant studies. We included only controlled trials and ultimately seven trials were included in our meta-analysis. Participants: Inclusion criteria included women undergoing gynecological laparoscopic surgery. Intervention: The intervention of direct trocar insertion technique compared with Veress needle entry technique. Main outcome measures: We compared five different outcomes associated with the efficacy and complications of laparoscopic entry. Results: The pooled analysis showed that Veress needle entry was associated with a significant increase in the incidences of extraperitoneal insufflation (RR=0.177, 95% Cl (0.094 to 0.333), p<0.001), omental injury (RR=0.418, 95% Cl (0.195 to 0.896), p<0.001), failed entry (RR=0.173, 95% Cl (0.102 to 0.292), p<0.001), and trocar site infection (RR=0.404, 95% Cl (0.180 to 0.909), p<0.029). There was no significant difference between the two groups regarding the visceral injury (RR=0.562, 95% Cl (0.047 to 6.676), p<0.648). Conclusions: When excluding all data apart from gynecologic surgery, the Veress needle entry technique may have an increased incidence of some, but not all complications of laparoscopic entry. It may also have a higher incidence of failed entry compared with direct entry techniques. Care should be taken in extrapolating these general results to specific surgeon experience levels. Trial registration number: CRD42021273726